Pemanfaatan Teknologi Digital oleh Majlis Ta’lim Darrussofa Medan dalam Melaksanakan Dakwah di Media Sosial: Use of Digital Technology by Majlis Ta'lim Darrussofa Medan in Carrying Out Da'wah on Social Media - Purnomo, Dwi Endar; Efendi, Erwan (QULUBANA: Jurnal Manajemen Dakwah, 2024)
The use of digital social media technology in da'wah has an important role and great potential. Through social media, da'wah messages can be spread quickly and effectively, reaching a wider audience. The aim of Majlis Ta'lim Darrushofa Medan is to utilize digital technology in carrying out da'wah on social media to provide knowledge, appreciation and behavioral guidance to the Muslim community in accordance with Islamic teachings. Through social media used by Majlis Ta'lim Darrushofa Medan with studies -studies that utilize social media to convey their preaching messages through social media by means of live streaming studies and also spreading their preaching content on several Majlis Ta'lim Darrushofa Medan media accounts such as the social media accounts TikTok, Instagram, YouTube, Facebook, and is also active in social activities, such as holding regular weekly studies at Medan city mosques. This research, which was conducted at Majlis Ta'lim Darrushofa Medan, used a qualitative approach. The use of social media in da'wah activities carried out by Majlis Ta'limDarrushofa Medan on social media has a very positive impact on social media users, where technology is developing so rapidly nowadays and Majlis Ta'lim Darrushofa Medan plays a significant role and has great potential.